2008
DOI: 10.1002/ab.20289
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and prosocial children's emotion attributions and moral reasoning

Abstract: Aggressive and prosocial children's emotion attributions and moral reasoning were investigated. Participants were 235 kindergarten children (M 5 6.2 years) and 136 elementary-school children (M 5 7.6 years) who were selected as aggressive or prosocial based on (kindergarten) teacher ratings. The children were asked to evaluate hypothetical rule violations, attribute emotions they would feel in the role of the victimizer, and justify their responses. Compared with younger prosocial children, younger aggressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 56 publications
(66 reference statements)
6
64
1
5
Order By: Relevance
“…Previous research indicated that children regard violations of negative moral duties as more severe than not following positive moral duties, such as not sharing (e.g. Malti, Gasser, & Buchmann, 2009). Thus, having to wait with one's response might have helped children to think about the victimizer's transgression in more detail and attribute negative emotions according to the perceived severity of the violation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that children regard violations of negative moral duties as more severe than not following positive moral duties, such as not sharing (e.g. Malti, Gasser, & Buchmann, 2009). Thus, having to wait with one's response might have helped children to think about the victimizer's transgression in more detail and attribute negative emotions according to the perceived severity of the violation.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy, like other moral emotions (e.g., shame and guilt), has been seen as a mediator of moral standards and behaviour (Tangney, Stuewig, & Mashek, 2007). Moral emotions appear to enable individuals to anticipate how moral transgressions will lead to deleterious outcomes, which assists in altering behaviour for a more positive result (Malti, Gasser, & Buchmann, 2009). Empathy in particular has been shown to be a factor that can inhibit antisocial behaviour (Cohen & Strayer, 1996;Hoffman, 2000;Miller & Eisenberg, 1988).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…They help children anticipate the negative outcomes of moral transgressions and enable them to adjust their moral behaviour accordingly (Malti, Gasser, & Buchmann, 2009).…”
Section: Moral Emotions and Bullyingmentioning
confidence: 99%